Study of the Phosphorus Adsorption on the Sediments - Hind Omari; Ali Dehbi; Adil Lammini; Abdelaziz Abdallaoui (Journal of Chemistry)
The objective of this work is to determine the reflection elements, allowing the understanding of the phosphorus fixation mechanisms. The samples were taken from Oued Boufekrane in the Meknes region (Northwest of Morocco). In fact, the sediment characterization was examined by the Brunauer–Emmett–Teller (BET) specific surface area and Fourier-transform infrared (FTIR) spectroscopy measurements. A series of experiments were then carried out to study the impact of some parameters on the adsorption capacity. Indeed, the effect of contact time, sediment mass, pH, initial concentration of potassium dihydrogen phosphate KH2PO4, and the temperature has been studied. The characterization of sediment by FTIR spectroscopy shows the existence of carbonates, iron hydroxides, and organic matter. The results obtained showed that the retention of phosphorus on the sediments studied is maximal at pH = 12 and increases with the temperature and the mass of sediments. Phosphorus adsorption kinetics of phosphorus on sediments studied follows the pseudo-second-order model, and the activation energy value (48.51 kJ/mol) indicates the predominance of chemical nature of adsorption (>40 kJ/mol). The experimental data of the adsorption isotherms are well interpreted by the Freundlich model. The values of the thermodynamic parameters ΔG°, ΔH°, and ΔS° indicate that the adsorption reaction is endothermic and occurs spontaneously on the surface of the sediments studied.